Analisis Pengaruh Cost Management Terhadap Efisiensi pada Proyek Konstruksi Studi pada Perusahaan PT. Adhi Karya (Persero) Tbk. - Pratiwi, Rahmawati Eka (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
Research on cost management on the efficiency that has been done by Ali and Kamaruzzaman (2010), Memon, Rahman, Aziz (2012), Olawale and Sun (2010), Ceylan (2008), Kasem and Alhaffar (2011), Marshall (2007), in which there are significant variables that showed different results, giving rise to a research gap. Therefore it is necessary to study more about the influence of these variables on the efficiency in cost management in construction projects. Research problem to be studied is to analyze the variables of cost management here is the estimated cost, experience project manager, contract management, cost of machinery or equipment, material price fluctuations, and owner funds, which affects the efficiency (cost performance index), which variables the largest and most significant influence.The study sample was taken from one of the construction projects of the state-owned company in Indonesia, PT. Adhi Karya (Persero) Tbk. between the years 2010-2013, so the number of samples (n) = 60. The sampling method using purposive sampling. Data using multiple regression analysis and hypotheses were tested by t test and F test with a significant level of 5%.This research seeks to examine the effect of the estimated cost (EB), experience of project manager (PPM), contract management (MK), the cost of the machine (BM), fluctuations in the price of materials (FHB), and fund owner (DO) on the efficiency of the project (cost performance index / CPI). The analysis showed that the data used in this study meets the classical assumptions, which include: distributed normal, multicollinearity does not happen, and not happen heterocedastity. From the results of the regression analysis also obtained partial results that the estimated cost, experience project manager, contract management, cost of machinery, material price fluctuations, and the owner fund a significant effect on the efficiency (cost performance index).